The Influence of Organizational Culture and Work Discipline on Employee Performance at the Palopo City Social Services Office - Winda, Winda; Adhelia, Adhelia; Rahmi, Rahmi; Nurjannah, Nurjannah; Edy, Khairunnisa (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
This study aims to determine and analyze the influence of organizational culture and work discipline on employee performance at the Social Services Office of Palopo City. The research problem addressed is how organizational culture and work discipline influence employee performance both partially and simultaneously. This study employed a quantitative method with an associative approach. The population consisted of all 32 employees of the Social Services Office of Palopo City, with the entire population taken as the sample (saturated sampling). Data collection techniques included observation, questionnaires, interviews, and documentation. Data analysis techniques comprised descriptive analysis, validity testing, reliability testing, multiple linear regression, t-test, F-test, and the coefficient of determination (R). The results indicate that organizational culture and work discipline have a positive and significant effect on employee performance. Partially, organizational culture has a significant effect on employee performance, with a significance value of 0.011 0.05, and work discipline also has a significant effect, with a significance value of 0.001 0.05. Simultaneously, the significance value of 0.000 0.05 shows that both independent variables together affect employee performance. The coefficient of determination (R) of 0.785 indicates that 78.5% of the variation in employee performance is influenced by organizational culture and work discipline, while the remaining 21.5% is influenced by other factors not examined in this study.